Implications of Ohio's 20-Week Abortion Ban on Prenatal Patients and the Assessment of Fetal Anomalies. Issue 5 (May 2017) - Farrell, Ruth M.; Mabel, Hilary; Reider, Mitchell W.; Coleridge, Marissa; Yoder Katsuki, Monique
Abstract : Ohio's governor recently signed into law Senate Bill 127, a bill that makes it a fourth-degree felony for a health care provider to perform an abortion "when the probable post-fertilization age of the unborn child is 20 weeks or greater, " joining a series of other states that have enacted such legislation or are moving toward similar legislation. Twenty-week bans have salient implications for women's health, quality of care, and access to services, particularly in the context of the delivery of prenatal care. Because of the timeline of the initiation of prenatal care and assessments of fetal genetic and anatomic anomalies, patients may increasingly find themselves at or near the 20-week postfertilization gestational threshold when they have insufficient information to decide about continuing or ending the pregnancy. This law thus leaves women and families with limited time to obtain a genetic or anatomic diagnosis, restricts access to abortion care at a crucial decision-making time in the pregnancy, and has significant implications for the patient–physician relationship. This law also has ramifications for women and health care providers outside of Ohio, because patients who have made the choice to end a pregnancy will have to cross state lines for abortion care. It is important for obstetric providers to be aware of the ramifications of 20-week bans and take steps to ensure that pregnant women receive high-quality care despite the burdens imposed on the health care decision-making process. Abstract : Laws restricting women's access to pregnancy termination beyond 20 weeks postfertilization affect not only patient safety and health care quality but also the practice of obstetrics.